Oral Hygiene Practices, Lifestyle Determinants, and Epidemiological Patterns of Hypertension in Urban Adults - Touseef Ansar, Saleem Adil, Lubna Yousaf, Muhammad Akram Cheema, Misbah Ul Hasan Ghani, Mir Abdul Qadir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
This cross-sectional analytical study assessed associations between oral hygiene behaviours,lifestyle determinants and hypertension prevalence in urban adults. The objective was to quantifythe impact of toothbrushing frequency, use of oral products, smoking, diet and physical activity on blood pressure